2014
DOI: 10.1371/journal.pone.0110739
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Autoimmune Neuro-Inflammation in Mice Cured from Blood-Stage Plasmodium berghei Infection

Abstract: The thymus plays an important role shaping the T cell repertoire in the periphery, partly, through the elimination of inflammatory auto-reactive cells. It has been shown that, during Plasmodium berghei infection, the thymus is rendered atrophic by the premature egress of CD4+CD8+ double-positive (DP) T cells to the periphery. To investigate whether autoimmune diseases are affected after Plasmodium berghei NK65 infection, we immunized C57BL/6 mice, which was previously infected with P.berghei NK65 and treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…The thymic microenvironment integrity must be preserved to ensure the appropriate maturation of T cells since damage to this organ may implicate in inadequate repertoire of T cells in peripheral lymphoid organs, which in turn can lead to autoimmune diseases or immunosuppression. In this context, we have shown that experimental malaria infection leads to thymic atrophy in mice and turns mice susceptible to an aggravated form of experimental autoimmune encephalomyelitis (EAE), the experimental model of multiple sclerosis [ 24 ]. More recently, we found that acute infection with Pb yeast cells promotes thymic alterations that lead to a defective repertoire of peripheral T cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The thymic microenvironment integrity must be preserved to ensure the appropriate maturation of T cells since damage to this organ may implicate in inadequate repertoire of T cells in peripheral lymphoid organs, which in turn can lead to autoimmune diseases or immunosuppression. In this context, we have shown that experimental malaria infection leads to thymic atrophy in mice and turns mice susceptible to an aggravated form of experimental autoimmune encephalomyelitis (EAE), the experimental model of multiple sclerosis [ 24 ]. More recently, we found that acute infection with Pb yeast cells promotes thymic alterations that lead to a defective repertoire of peripheral T cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To get evidences for the mechanism that could be involved in this protective effect, we evaluated cytokine production, the percentage of regulatory T cells (Tregs) and myeloid DCs during both the early clinical (10th day) and clinical (17th day) EAE phases. Even though only more recently explored, alterations present at the EAE onset or early clinical disease phase are relevant to determine the involvement and kinetics of different cell types and their mediators in disease aggravation or disease control . The relevance of this early analysis was very clear in our study.…”
Section: Discussionmentioning
confidence: 77%
“…Gene expression analysis was performed as previously described . Briefly, RNA was extracted from tissues using TRIzol reagent according to manufacturer's recommendations (Life Technologies, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%